Analisis Struktur Kristal Polyetilen Glicol (PEG-4000) Coated Nanopartikel Magnetite (Fe3O4) - Alfrie Musa Rampengan; Jeferson Polii (Jurnal Kimia Fullerene, 2019)
The synthesis of materials made from FeSO4.7H2O, FeCl3.6H2O, and NH4OH hydrophilic materials has been carried out using coprecipitation method to produce Fe3O4 nanoparticle material. Analysis of the crystalline structure of Fe3O4 nanoparticles seen from the results of material characterization using X-Ray Diffractometer showed diffraction peaks namely (220) (311) (400) (511) (440) with the main peak at the index (311). Samples of Fe3O4 nanoparticles were modified with PEG-4000 polymer, emerging new diffraction peaks such as peaks with index (111), α- Fe3O4 peaks, γ-FeO (OH) peaks and α-FeO ​​(OH) peaks. The emergence of these new peaks is due to the influence of the PEG-4000 polymer which directly shows the bond with the -OH (hydroxyl) group.